CRAN-25. METASTATIC CHOROID PLEXUS CARCINOMA WITHOUT ADJUVANT TREATMENT WITH GOOD SURVIVAL: A CASE REPORT. Issue 2 (22nd June 2018) - Carter, Lacey; Gross, Naina
Abstract: Three-year-old previously healthy female presented with drowsiness and vomiting found to have a 3.6x5.1x6.1cm enhancing solid, partially cystic mass centered within the atrium of the right ventricle and an enhancing intradural mass at S1/S2 with enhancement of nerve roots concerning for leptomeningeal carcinomatosis. Patient underwent subtotal resection of the ventricular mass determined to be choroid plexus carcinoma with associated p53 mutation. Family elected palliative care. Patient had an Ommaya reservoir placed for intermittent removal of CSF for headaches. After developing elevated intracranial pressure not relieved by drainage, patient underwent repeat subtotal resection thirty-one months after initial resection. Microscopic examination in the original tumor was difficult due to crush artifact which obscured any mitoses, but demonstrated severe pleomorphism and was invasive into surrounding neural tissue. The tumor was positive for p53, Kir7.1, synaptophysin, and CAM5.2 and negative for PLAP, glypican-3 and EMA. Frequency of Ki67/Mib-1 immunolabeling was variable, but focally high. Despite the lack of obvious mitotic activity, given p53 and Ki67/Mib-1 immunolabeling, patient was diagnosed with choroid plexus carcinoma. Specimen from second resection showed the same results. Patient presented with multiple poor prognostic factors including p53 mutation, metastasis at presentation, subtotal resection, and no adjuvant treatment. Meta-analysis indicates subtotal resection without adjuvant treatment leads to estimated median survival of less than five months. Patient has not only survived, but has done very well. This case illustrates a clinical course that does not match the predicted disease course for the pathologic diagnosis. Further delineation of these tumors is needed.